Measuring the Dispositional Tendency to Spread Oneself Too Thin - Boemerman, Louis; Kuykendall, Lauren (Frontiers in Psychology, 2018)
This paper describes the development and validation of a scale to measure the dispositional tendency to spread oneself too thin (SOTT)—a tendency that is likely an important antecedent of work-nonwork conflicts. In two studies, we develop and validate a scale for measuring this tendency and examine how it relates to other dispositional causes of role conflicts. In Study 1 we tested our initial item pool using a heterogeneous sample of full-time workers (N=193) and used exploratory factor analysis to reduce our item pool to a set of five items. In Study 2, using another heterogeneous sample of full-time workers (N=212), we conducted confirmatory factor analyses to demonstrate that the items fit a unidimensional construct. We also demonstrated that the scale has moderately high test-retest reliability, is distinct from other potentially related constructs, and predicts work-nonwork conflicts above and beyond previously studied dispositional antecedents. We discuss the importance of studying the dispositional tendency to spread oneself too thin as a potentially malleable antecedent of work-nonwork conflict and note other employee outcomes that it may also impact.